Maternal urinary cadmium levels during pregnancy associated with risk of sex-dependent birth outcomes from an e-waste pollution site in China - Zhang, Yuling; Xu, Xijin; Chen, Aimin; Davuljigari, Chand Basha; Zheng, Xiangbin; Kim, Stephani S.; Dietrich, Kim N.; Ho, Shuk-Mei; Reponen, Tiina; Huo, Xia (Reproductive toxicology (Elmsford, N.Y.), 2018)
•We firstly reported Cd associated with sex-specific difference in birth outcomes of neonates from an e-waste recycling area.•The maternal urine Cd concentrations were much higher in Guiyu group than that in the referenced group.•E-waste recycling activities and residence in an e-waste area during pregnancy might result in elevated Cd concentrations.•Cd levels negatively correlated with birth weight, length, head circumference and Apgar scores in female newborns. This study was to investigate whether exposure to cadmium (Cd) during pregnancy is associated with an increased risk of adverse birth outcomes in a sex-dependent manner. Cd concentrations in maternal urine (U-Cd) samples were measured in 237 subjects from Guiyu (e-waste area) and 212 subjects from Haojiang. A significance level of p <0.05 was used for all analyses. The maternal U-Cd levels in Guiyu residents were significantly higher than Haojiang. We found significant inverse associations between U-Cd concentrations and birth anthropometry (birth weight, birth length, Head Circumference and Apgar scores with 1min and 5 mins) in female neonates, but no significant associations were observed in male neonates except Apgar (1min) score after adjustment. The association was more pronounced among female neonates than male neonates, suggesting an association between Cd and adverse birth outcomes may be sex-specific.